Development and diversity of Andean-derived, gene-based microsatellites for common bean (Phaseolus vulgaris L.) - Blair, Matthew W.; Muñoz Torres, Mónica Cecilia; Giraldo, M.C.; Pedraza, F (Springer, 2009)
Background: Gene-based (genic) microsatellites are a useful tool for plant genetics and simple sequence repeat loci can often be found in coding regions of the genome. While EST sequencing can be used to discover genic microsatellites, direct screening of cDNA libraries for repeat motifs can save on overall sequencing costs. The objective of this research was to screen a large cDNA library from and Andean common bean genotype for six di-nucleotide and tri-nucleotide repeat motifs through a filter hybridization approach and to develop microsatellite markers from positive clones. Results: Robotics were used for high-throughput colony picking and to create a high-density filter of 18,432 double spotted cDNA clones which was followed by hybridization with repeat motif containing probes based on GA, CA, AAT, CAG, CAA and ACG repeats. A total of 1203 positive clones were identified by their addresses and sequenced from 5' ends and if required from 3' ends to confirm repeat motif and length. Out of 886 high quality sequences, 497 had complete microsatellite loci that were not truncated by the sequencing reaction and of these tri-nucleotide repeats were more common than di-nucleotide repeats. Different motifs were found in different frequencies in the 5' and 3' ends of the cDNAs. In a microsatellite development program, primers were designed for 248 SSR loci which were tested on a panel of 18 common bean genotypes to determine their potential as genetic markers finding higher average polymorphism information content for di-nucleotide repeat markers (0.3544) than for tri-nucleotide repeat markers (0.1536). Conclusion: The present study provides a set of validated gene-based markers for common bean that are derived from G19833, an Andean landrace that is an important source of disease and abiotic stress tolerance which has been used for physical map development and as a mapping parent. Gene-based markers appear to be very efficient at separating divergent wild and cultivated accessions as well as Andean and Mesoamerican genepools and therefore will be useful for diversity analyses and for comparative and transcript mapping in common bean.